Assesing and maping forest fire risk in Bejaia, Algeria, using GIS tehnique and remote sensing - Sallaye Miloud; Belloulou Bilal; Khallef Boubaker (Glasnik Srpskog Geografskog Društva)
Each year, Forest fires pose significant socio-economic and environmental challenges, particularly in Mediterranean regions. In this respect, the wilaya of Bejaia, located in the northeastern part of Algeria, is an illustrative example of forest fires. In this study, we used multi-source remote sensing data (MODIS, Landsat 8) and the Google Earth Engine (GEE) platform to assess and map the burn severity of forest fires that occurred in 2021. In addition, the Normalized Difference Vegetation Index (NDVI) and the Differenced Normalized Burn Ratio (dNBR) were applied to identify and analyze severity and extent of the damage. Results showed that approximately 15281.86 hectares, (4.69 % of the study area) were burned, with 7156.33 hectares classified as high-severity burns, mostly located in the northwestern part of the region, such as Adekar, El Kseur, and Kendera. Further analysis showed that topographical and environmental factors such as elevation, aspect and slope played a significant role in fire propagation. This research shows how GIS and remote sensing can be valuable tools for policymakers in designing targeted strategies for fire prevention and mitigation in high-risk areas.